Outcome of Snodgrass Repair in Distal Hypospadias – An Institutional Experience (Journal of Society of Surgeons of Nepal, 2018)
Introduction: Hypospadias is a common congenital anomaly in which the urethral opening is on the ventral surface of the penis, often associated with ventral curvature of penis (chordee). Many techniques have been descried in the literature for the repair of hypospadias with variable results. This study aimed at outcome following Snodgrass repair in distal hypospadias by a single Urologist.Methods: This was a retrospective study conducted at Department of Urology, Birat Medical College from December 2017 to January 2019 during which 16 patients with distal hypospadias underwent primary repair using Snodgrass technique.Results: Mean age was 5.12 years and duration of operation was 136.25 minutes. About 56.25% of cases were subcoronal and 43.25% were coronal. Chordee of